Algorithm to calculate or approximate the Square Root of a positive real number: Algoritmo para calcular o aproximar la Raíz Cuadrada de un número real positivo - R, Jesús R Guillén (2019)
In this article a variant of the traditional algorithm for the calculation of the square root is developed, that like the traditional algorithm is based on the decimal decomposition of the number, but in its execution the elements of the formal demonstration of this algorithm are used, giving an alternative that improves the process of understanding it. In this research a detailed study is presented through several algorithmic-based results that allow us to delve into the compression of the process of calculating or approximate the square root of a positive real number, which makes the article have a university target audience.